Afghan frontier: understanding tobacco practices among migrant population in India - Rashmi Mehra; Vikrant Mohanty; Aswini Y Balappanavar; Karn Mehra; Shivam Kapoor; Vaibhav Gupta (Tobacco Induced Diseases, 2018)
Background According to the World Refugee Survey by US Committee for Refugees and Immigrants, migrants from Afghanistan constitute the 4 th largest group of migrants to India. No previous studies have been conducted to assess the tobacco consumption status and pattern among this migrant population. Hence the aim of our study was to understand the tobacco use patterns and barriers among the migrant population from Afghanistan.